Epigenetic «probes» for lung cancer monitoring: LINE-1 methylation pattern in blood- circulating DNA - A. A. Ponomaryova; Е. Y. Rykova; N. V. Cherdyntseva; A. A. Bondar; A. Y. Dobrodeev; A. A. Zavyalov; S. A. Tuzikov; L. O. Bryzgalov; T. I. Merkulova; V. V. Vlassov; P. P. Laktionov (Вавиловский журнал генетики и селекции, 2015)
Malignant cell transformation is accompanied by two processes of DNA methylation changes: promoter hypermethylation of specific genes and hypomethylation of retrotransposons. The composition of circulating DNA (cirDNA) from plasma and cell-surface-bound circulating DNA (csb- cirDNA) was shown earlier to be altered in the blood of cancer patients due to accumulation of tumor- specific aberrantly methylated DNA fragments, which are currently considered valuable cancer markers. The present study compares LINE-1 retrotransposon methylation patterns in plasma cirDNA and csb- cirDNA from 21 untreated lung cancer patients (LC) and 23 healthy donors. Concentrations of methylated LINE-1 region 1 copies (LINE-1met) were assayed by real-time methylation-specific PCR. In order to normalize the LINE-1 methylation level, the LINE-1 region 2 concentration was evaluated, which was independent of the methylation status (LINE-1Ind). The LINE-1met concentration in csb-cirDNA tended to decrease (by a factor of 1.4) in blood from LC patients in comparison to healthy donors (Mann- Whitney test, P=0.16). The LINE-1Ind concentration in csb-cirDNA (methylation-independent) was found to be threefold lower in LC patients and fourfold lower in patients with adenocarcinoma than in healthy donors. That is why, along with the expected decrease in LINE-1met concentration in csb-cirDNA, we recorded an unexpected statistically significant increase of the LINE-1 methylation index determined as (LINE-1met/LINE-1Ind) due to the profound LINE-1Ind decrease. Plasma cirDNA demonstrated no difference in the LINE-1 methylation index (LINE-1met/LINE-1Ind) between LC patients and healthy donors (Mann-Whitney test, P = 0.40). The data obtained agree with our earlier results, which showed that csb-cirDNA was a highly informative material for lung cancer diagnostics.